Impact of Herpes Zoster and Postherpetic Neuralgia on the Quality of Life in China: A Prospective Study - Liu Y; Liu H; Bian Q; Zhang S; Guan Y (Dove Medical Press, 2024)
Yong Liu,1 Hui Liu,2 Queqiao Bian,1 Shuhuan Zhang,1 Yanmin Guan3 1Department of Dermatology & STD, The Third Central Hospital of Tianjin; Tianjin Key Laboratory of Extracorporeal Life Support for Critical Diseases; Artificial Cell Engineering Technology Research Center; Tianjin Institute of Hepatobiliary Disease, Tianjin, People's Republic of China; 2Tianjin Institute of Hepatobiliary Disease, The Third Central Hospital of Tianjin, Tianjin, People's Republic of China; 3Department of Tuberculosis, Tianjin Haihe Hospital, Tianjin, People's Republic of ChinaCorrespondence: Yong Liu, Department of Dermatology & STD, The Third Central Hospital of Tianjin; Tianjin Key Laboratory of Extracorporeal Life Support for Critical Diseases; Artificial Cell Engineering Technology Research Center; Tianjin Institute of Hepatobiliary Disease, No. 83, Jintang Road, Hedong District, Tianjin, 300170, People's Republic of China, Email liuyongtj@163.comBackground: Herpes zoster (HZ) and postherpetic neuralgia (PHN) significantly affect patients' quality of life (QoL). Cultural differences may lead to different patient-reported outcomes across countries. The current study aims to evaluate the detrimental impact of HZ and PHN on QoL in China.Methods: This prospective study was conducted from January 2020 to April 2023. We used the Zoster Brief Pain Inventory (ZBPI) and 5-level EuroQol-5 Dimension (EQ-5D-5L) questionnaire to assess the QoL of HZ and PHN patients. Patients were required to complete the questionnaires at 15, 30, 60, and 90 days after the onset of the HZ rash. Additional questionnaires were administered at 120, 150, and 180 days for those who developed PHN within three months of the rash's onset.Results: A cohort of 633 patients with a median age of 63 years were included in the study. The mean delay from the appearance of the initial HZ rash to the first medical consultation was 5.1 ± 2.8 days. Approximately 30% of the HZ patients (189/633) went on to develop PHN. For patients with HZ who did not progress to PHN, the ZBPI worst pain score and impaired QoL had nearly resolved by day 90 post-rash onset. Conversely, there was no significant improvement in the ZBPI worst pain score and QoL for those with PHN, even by day 180 post-rash onset.Conclusion: Both HZ and PHN significantly impaired patients' QoL. However, the impairment caused by PHN was more severe in both intensity and duration.Keywords: herpes zoster, pain, post-herpetic neuralgia, quality of life